Seroprevalence of specific antibodies to Treponema pallidum in blood donors with DNA confirmation of seropositivity: Antibody seroprevalence of T. pallidum in blood donors - T. Nanakaly, Haween; A. Dzayee, Shireen; M. Said, Ashti; S. Qader, Saleem (Cellular and Molecular Biology, 2025)
The rising global incidence of syphilis underscores the risk of transmission through blood transfusions. Treponema pallidum, the pathogen responsible for syphilis, represents a major public health challenge. Accurate detection is essential for controlling the disease, particularly in asymptomatic blood donors. This study aimed to evaluate the seroprevalence of specific antibodies against T. pallidum in blood donors, confirmed by DNA testing for seropositivity. The goal was to enhance our understanding of syphilis exposure and improve the safety of blood donations. A total of 1,260 HIV, HCV, and HBsAg-negative blood donors were screened for T. pallidum-specific antibodies using enzyme-linked immunosorbent assay (ELISA). Initially, reactive samples were re-evaluated, and those repeatedly reactive were classified as seropositive for syphilis. ELISA-positive samples were further tested for T. pallidum DNA using real-time polymerase chain reaction (RT-PCR). Data analysis was done using SPSS with a level of significance p< 0.05 Of 1,260 blood donors, the seroprevalence of anti-T. pallidum antibodies was 0.158%, with both positive cases confirmed by PCR. The prevalence was 0.2% in males and 0.00% in females, with no significant gender differences (P > 0.05). The highest prevalence was in the 31-40 age group (0.5%), but this was not statistically significant (P > 0.05). There were no significant differences by donation type or marital status. Significant associations were observed with educational level (P < 0.05), with higher prevalence among high school graduates Our results confirm syphilis in Iraqi blood donors, highlighting the need for routine T. pallidum ELISA screening at transfusion centers. Positive cases should be discarded and affected donors treated. ELISA is an effective primary screening method, consistent with WHO guidelines for low-prevalence settings, and is essential for preventing transfusion transmission.